Melt-electrowritten scaffolds containing hydroxyapatite for guided bone tissue regeneration - Ferreira, Marta Albuquerque Cristóvão (2022)
Melt-electrowriting (MEW) is an emerging technology that has been developed to produce scaffolds with three-dimensional ordered, precise and porous structures with fibre size smaller than 100 μm. Calcium phosphates facilitate bone growth and improve scaffolds bioactivity, which is essential for bone tissue engineering. Incorporating calcium phosphate particles, such as hydroxyapatite (HAp), into fibrous scaffolds is therefore desirable. However, this remains a challenge in MEW as HAp particles can agglomerate and hinder a continuous printing process. The polymer poly(ε-caprolactone) (PCL) and the copolymer of ε-caprolactone/ lactic acid (PCL/PLA) were selected as materials in this work. In the first part of the work, PCL and PCL/PLA were characterised, and it was observed that the copolymer exhibits slight thermal degradation when heated. Moreover, the copolymer showed a lower Young modulus than PCL. Melt-electrowritten scaffolds were produced with both polymers. PCL scaffolds showed aligned fibres, while PCL/PLA scaffolds had misaligned fibres and decreased porosity compared to PCL scaffolds. In the second part of this work, blends of the two polymers with two types of HAp powders – a nanoHAp and a microHAp – were produced. After characterization, the blends demonstrated a HAp particles’ loading near the planned amount (3.5 wt%), and the addition of HAp particles enhanced the Young modulus compared to the plain polymer. The printing parameters for MEW were optimised with the produced blends, and composite melt-electrowritten scaffolds were printed. PCL composite scaffolds with a pore size of 500 μm demonstrated aligned fibres with defined porosity. PCL/PLA-microHAp composite melt-electrowritten scaffolds never described in the literature before were produced in this work. The scaffolds did not present aligned fibres, nevertheless, this study represents an important advance in the optimization of the printing process. PCL/PLA-nanoHAp scaffolds were not possible to print due to particle agglomeration. The tendency of nano-HAp to agglomerate disrupted the printing process, whereas the micro-HAp agglomerated less and proved superior performance for scaffold production by MEW. The scaffolds were seeded with human mesenchymal stem cells and allowed their attachment and proliferation, showing potential for bone tissue engineering.